2018
DOI: 10.1186/s12862-018-1185-2
|View full text |Cite
|
Sign up to set email alerts
|

Origin, evolution, and divergence of plant class C GH9 endoglucanases

Abstract: BackgroundGlycoside hydrolases of the GH9 family encode cellulases that predominantly function as endoglucanases and have wide applications in the food, paper, pharmaceutical, and biofuel industries. The partitioning of plant GH9 endoglucanases, into classes A, B, and C, is based on the differential presence of transmembrane, signal peptide, and the carbohydrate binding module (CBM49). There is considerable debate on the distribution and the functions of these enzymes which may vary in different organisms. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 119 publications
1
15
0
Order By: Relevance
“…The microfibrillar structure of cellulose is constituted and strengthened by islands of hydrogen-bonded inter-glucan chains. These microcrystalline regions ( I α , I β ) render cellulose chemically inert and recalcitrant to most physical stressors, an attribute that is desirable to land plants (xylem, phloem), sporulating bacteria and fungi, and quorum sensing by microbial biofilms [ 1 8 ]. Most organisms (bacteria, fungi, protists) possess enzymes (oxidoreductases, EC 1.x.y.z; transferases, EC 2.x.y.z; hydrolases, EC 3.x.y.z) that can cleave cellulose into physiologically relevant oligo- and mono-saccharides (RXNs 1 – 3 ) [ 2 , 9 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The microfibrillar structure of cellulose is constituted and strengthened by islands of hydrogen-bonded inter-glucan chains. These microcrystalline regions ( I α , I β ) render cellulose chemically inert and recalcitrant to most physical stressors, an attribute that is desirable to land plants (xylem, phloem), sporulating bacteria and fungi, and quorum sensing by microbial biofilms [ 1 8 ]. Most organisms (bacteria, fungi, protists) possess enzymes (oxidoreductases, EC 1.x.y.z; transferases, EC 2.x.y.z; hydrolases, EC 3.x.y.z) that can cleave cellulose into physiologically relevant oligo- and mono-saccharides (RXNs 1 – 3 ) [ 2 , 9 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glycoside hydrolase 9 (GH9) endoglucanases ( EC 3.2.1.4) hydrolytically cleave the β (1 → 4)-glycoside linkage between contiguous ( D )-glucopyranose residues and accomplish this with the aid of one or more carbohydrate binding modules (CBMs). Detailed phylogenetics analysis and molecular dating has shown that GH9 (≅480 AA ) is very well conserved amongst taxa and has been so for ≈3000 Mya [ 8 , 17 ]. The presence of active site residues in GH9 further imply that catalysis of crystalline cellulose proceeds by a relatively unchanged generic acid-base mechanism and may deploy aspartic ( D ) and/or glutamic ( E ) acids as alternating proton donors/acceptors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations